Pentingnya Sekolah dalam Perjanjian Lama - Philipus Benitius Metom (Kanisius, 2023)
The Old Testament Scriptures use a number of terms that reveal that the people of the Old Testament were already familiar with education and teaching. These activities were the main activities of schools. The author therefore asks the following questions: Was there a school in the life of the Old Testament people? Why was school important in the life of the Old Testament people? Why were teaching, talking and writing about loving God with all your heart, all your soul and all your strength important in the life of the Old Testament people? These three questions prompted the author to seek out the research objectives of knowing the importance of school in the lives of the Old Testament people, and knowing the benefits of school that were seen as important by the Old Testament people. After elaborating a number of thoughts, the author finally draws the conclusion that the Old Testament people were familiar with schools in their lives and considered the existence of formal schools and informal schools important because these two school models could educate and teach the children of Israel to know and fulfill the contents of the commandments of the Shema Israel (cognitive aspect). The importance of school is also closely related to its benefits to love the Lord God with all our heart (affective aspect), all our soul (spiritual aspect) and all our strength (psychomotor aspect).